Hubungan Antara Kecemasan Dan Pola Makan Dengan Kejadian Hiperemesis Gravidarum Pada Ibu Hamil - Retno Kumalasari (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Maternal Mortality Rate (MMR) is one indicator of a nation's health. During pregnancy, there are physiological changes in pregnant women which include physical, psychological and social changes. Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women. Anxiety and eating patterns are the determining factors causing the occurrence. Hyperemesis gravidarum. This type of research is a quantitative descriptive analytic study with a cross sectional epidemiological investigation approach. . The independent variables are anxiety and eating patterns. While the dependent variable is the incidence of hyperemesis gravidarum. The population of this study were all pregnant women patients in the KIA Room of Kaligondang Public Health Center, Purbalingga Regency as many as 60 people. The results showed a significant relationship between anxiety and eating patterns with the incidence of hyperemesis gravidarum at the Kaligondang Public Health Center, Purbalingga Regency. Diet and anxiety are one of the causes of hyperemesis gravidarum experienced by pregnant women in Kaligondang Public Health Center patients.